Physician Attitudes and Perceptions of Complementary and Alternative Medicine (CAM): A Multicentre Italian Study - Berretta, Massimiliano; Rinaldi, Luca; Taibi, Rosaria; Tralongo, Paolo; Fulvi, Alberto; Montesarchio, Vincenzo; Madeddu, Giordano; Magistri, Paolo; Bimonte, Sabrina; Trovò, Marco; Gnagnarella, Patrizia; Cuomo, Arturo; et al. (Frontiers in Oncology, 2020)
Purpose: Complementary and Alternative Medicine (CAM) interventions are widely used by patients with chronic disorders, including cancer, and may interact with cancer treatment. Physicians are often unaware of this, probably due to poor patient-physician communication on CAM. The purpose of this study was to evaluate physicians' knowledge, attitudes and practice patterns regarding CAM in a survey conducted in Italy. Methods: A questionnaire was administered to 438 physicians (11 Italian hospitals) who predominantly treat patients with chronic disease, to collect personal and professional data and information on attitudes toward CAM and its possible role in Conventional Medicine (CM). Results: Of the 438 participants, most were specialists in oncology (18%), internal medicine (17%), surgery (15%), and radiotherapy (11%). Most worked at university (44%) or research hospitals (31%). Forty-two percent of participants believed that CAM could have an integrative role within CM. Oncologists were the physicians who were best informed on CAM (58%). Physicians working at research institutes or university hospitals had a greater knowledge of CAM than those employed at general hospitals (p < 0.0001), and those who were also involved in research activity had a greater knowledge of CAM than those who were not (p < 0.003). Length of work experience was significantly related to CAM knowledge. Moreover, 55% of participants suggest CAM interventions to their patients and 44% discuss CAM with them. The best-known interventions were acupuncture, Aloe vera and high-dose vitamin C. Conclusion: CAM use by patients with chronic disease and/or cancer has become a topical issue for the scientific community and for physicians. Knowing the reasons that prompt these patients to use CAM and guiding them in their decisions would improve treatment and outcomes and also benefit healthcare systems. Our findings contribute to a greater understanding of CAM knowledge, attitudes, and practice among Italian physicians. Further research is needed to identify the more effective CAM treatments and to work toward an integrated healthcare model.